Using social media for job search: Evidence from generation Y job seekers - Manroop, L.; Richardson, Julia (2013)
Purpose — This study aims to investigate the extent to which Generation Y job seekers use social media to enhance their job search experience. Design/Methodology/Approach — The chapter draws on an in-depth analysis of qualitative data gathered from 29 interviews with recent university graduates in Human Resource Management (HRM). Findings — The findings of this study challenge popular stereotypes and anecdotes which seem to suggest that the power of technology come naturally and easily to Generation Y users (The Economist, 2010). It also suggests that young people, particularly graduates are unprepared for the job market. Many of them are stuck in the traditional ways of looking for a job despite the information that is available for them to exploit modern technologies to enhance their job search experience. Implications—Colleges and universities should include modern job search techniques such as social media into their curricula. In addition, career centers and employers need to play their part in disseminating information about how social media can be used by graduates to search for jobs. Originality/Value — The study emphasizes the need for individual users to exploit technology such as social media to enhance their professional and career success.